Design and Construction of Flap Type Wave Maker Using Servo-Motor Equipped with The Reducer for Generating Waves in 3-D Wave Tank - Mochammad Meddy Danial; Seno Darmawan Panjaitan; Arfena Deah Lestari; Jasisca Meirany; Teguh Suratman; Muhammad Abqari (International Journal of Offshore and Coastal Engineering, 2023)
Laboratory physical models in ocean engineering field are beneficial methods to conduct various research experiments. One of the most important equipment in the ocean engineering laboratory is a wave maker to generate and mimic the actual ocean wave. This research aims to design and construct a wave maker to generate waves on the wave tank with the dimensions of 7.5 m x 15 m x 1 m. The selected type of wave maker is a flap with hinged at the bottom, which is driven by a 3-phase motor 5 HP and gearbox reducer WPA 80 with a ratio of 1:40. The flap was connected to pulley B1-12 by shaft. There are three designs of wave maker system, i.e., stroke length of 0.5 m and the gearbox reducer with ratio 1: 40; stroke length of 0.5 m and the gearbox reducer with vbelt and pulley; stroke length of 0.05 m and the gearbox reducer with ratio 1: 40. The performance of the wave maker shows that the third design is more satisfying and suitable than the two others. However, the absorption structure must be added from both ends of the wave tank to reduce the wave reflection.